Ustekinumab Is Effective for the Treatment of Crohn's Disease of the Pouch in a Multicenter Cohort. Issue 4 (5th October 2018) - Weaver, Kimberly N; Gregory, Martin; Syal, Gaurav; Hoversten, Patrick; Hicks, Stephen Bradley; Patel, Devin; Christophi, George; Beniwal-Patel, Poonam; Isaacs, Kim L; Raffals, Laura; Deepak, Parakkal; Herfarth, Hans H; et al.
Abstract: Background: Crohn's disease (CD) of the pouch and chronic pouchitis occur in approximately 10% of patients after ileal pouch–anal anastomosis (IPAA) for refractory ulcerative colitis (UC) or UC-related dysplasia. The efficacy of anti–tumor necrosis factor (anti-TNF) agents and vedolizumab have been reported for the treatment of CD of the pouch and chronic pouchitis, but little is known regarding the use of ustekinumab in these settings. Our primary aim was to evaluate the efficacy of ustekinumab for these conditions. Methods: This is a retrospective, multicenter cohort study evaluating the efficacy of ustekinumab in patients with CD of the pouch and chronic pouchitis. Clinical response or remission was judged by the treating physician's assessment at 6 months. Results: Fifty-six patients (47 with CD of the pouch and 9 with chronic pouchitis) were included the study. Of these, 73% had previously been treated with either anti-TNF therapy, vedolizumab, or both after IPAA. Among patients with CD of the pouch and chronic pouchitis, 83% demonstrated clinical response 6 months after induction with ustekinumab. Responders demonstrated significantly less pouch inflammation on endoscopy when compared with nonresponders (29% vs 100%; P = 0.023). Higher mean body mass index at induction (26.3 vs 23.7; P = 0.033) and male sex (83% vs 30%; P = 0.014) were significant predictors of nonresponse to ustekinumab in those with CD of the pouch. Conclusion: In this refractory patient population, ustekinumab appears to be a safe and effective treatment for chronic pouchitis and CD of the pouch in biologic-naïve patients and those with prior anti-TNF or vedolizumab therapy failure.